One step ahead education of the gifted and talented - Greenberg, Gary; Reynolds, Maynard (Minnesota : University of Minnesota [production company] ; Nebraska : Great Plains National [distributor], 1986)
Explain about the gifted children, identification and education of gifted children
prog. 1. History of the gifted movement - prog 2. Definitions & character of giftedness - prog. 3. Identification of the gifted & talented - prog. 4. Organizational patterns for developing giftedness - prog. 5. Organizational patterns for the development of giftedness - prog. 6. Curriculum differentiation - prog. 7. Content differentiation : product & learning - prog. 8. Differentiation in social studies & the visual / performing arts - prog. 9. Differentiation in language arts, mathematics and science - prog. 10. Specific populations and areas of concern in gifted education
Keywords: Gifted children; Gifted person